A literatura poética nas escolas de ensino médio: uma análise das potencialidades da poesia na formação do jovem - Amaral, Isabel da Silva (2012)
This research aims to investigate the potential of poetic literature in the formation of critical consciousness among young people and is based on the concepts of Critical Theory of Society. The guiding hypothesis is that the subjects with higher poetic reception also tend to have a higher level of selfawareness. To verify this hypothesis was constructed and validated a scale of attitude, called Art, Education and Self-consciousness, which is divided into subscales: Self-consciousness and poetic reception. The scale and a questionnaire informative history of life were applied in 120 high school students in a public school located in the outskirts of São Paulo. The results indicate that is not possible to establish a direct correlation between selfassessment and poetic, although some important associations have been verified. Among them stands out the relationship between the average of the subjects with high levels of self-awareness and appreciation of poetry and the habit of reading poetry literature, and the insertion of the subject in the aesthetic universe. We highlight the socioeconomic status as a decisive factor for these little contact of these young subjects with the aesthetic, and the importance of offering the most diverse artistic activities, in regular courses and extracurricular, schools and public spaces